Polemik Hak Cipta Lagu Dewa 19 : Konflik Hukum Antara Ahmad Dhani dan Once Mekel - Mohamad Daniel Hokon; Nisa’anida Ainur Rosyidah; Nurita Putri Ramadani; Putri Candraningtyas; Emma Yunika Puspasari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Copyright is a right that provides protection for intellectual works in the fields of literature, writing, science and art. This research discusses the issue of copyright infringement that arises between Ahmad Dhani as the creator and copyright holder of songs belonging to the music group Dewa 19 and the former vocalist of Dewa 19, namely Once Mekel. The problem arose because Once Mekel had sung and performed Dewa 19 songs several times without permission to Ahmad Dhani. Both parties have different points of view regarding the obligation to use the song's copyright. This research aims to analyze copyright violations based on Law Number 28 of 2014 and examine the settlement achieved through mediation between the two parties. This research uses a normative legal approach with case studies. Therefore, singing songs without permission and without paying royalties is a violation of copyright and economic rights. Even though there were differences in interpretation of the provisions of copyright law between the two parties, they were decided through mediation. It is hoped that this research will be able to provide more comprehensive insight regarding the principles of song copyright and legal protection mechanisms in Indonesia.